2003
DOI: 10.1016/s0042-6822(03)00526-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of CRM1-mediated export for adenovirus gene expression

Abstract: A complex of the Adenovirus (Ad) early region 1b 55-kDa (E1b-55kDa) and early region 4 ORF6 34-kDa (E4-34kDa) proteins promotes viral late gene expression. E1b-55kDa and E4-34kDa have leucine-rich nuclear export signals (NESs) similar to that of HIV Rev. It was proposed that E1b-55kDa and/or E4-34kDa might promote the export of Ad late mRNA via their Rev-like NESs, and the transport receptor CRM1. We treated infected cells with the cytotoxin leptomycin B to inhibit CRM1-mediated export; treatment initially del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
5
16
0
Order By: Relevance
“…Consistent with previous observations (11,25,62), our findings demonstrated that inhibition of CRM1-mediated export of E1B-55K or E4orf6 has no effect on viral late mRNA export. Rather, the NES present in E1B-55K and E4orf6 are differentially required for the export of p53 and Mre11, two important cellular targets of the adenovirus-dependent cell-specific E3 ubiquitin ligase, indicating that although dispensable for viral late mRNA export, CRM1 is required for other activities that depend on E1B-55K/E4orf6 shuttling (44,69).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous observations (11,25,62), our findings demonstrated that inhibition of CRM1-mediated export of E1B-55K or E4orf6 has no effect on viral late mRNA export. Rather, the NES present in E1B-55K and E4orf6 are differentially required for the export of p53 and Mre11, two important cellular targets of the adenovirus-dependent cell-specific E3 ubiquitin ligase, indicating that although dispensable for viral late mRNA export, CRM1 is required for other activities that depend on E1B-55K/E4orf6 shuttling (44,69).…”
supporting
confidence: 93%
“…To address the role of CRM1 in E1B-55K and E4orf6-mediated viral mRNA transport, the CRM1 inhibitor LMB was used, which associates covalently to cysteine 528 in the NES binding region of CRM1 and thereby irreversibly blocks its interaction with NES containing proteins (26,47). These experiments showed that the functional inhibition of CRM1 by LMB had only a minor effect on viral late protein synthesis (an indirect measurement of viral late mRNA export), leading to the conclusion that LMB treatment during the late phase of adenoviral replication does not abrogate viral late mRNA accumulation in the cytoplasm (11,62). A different experimental approach, in which a specific peptide inhibitor of CRM1 was used to make direct measurements of viral late mRNA export, supported these findings.…”
mentioning
confidence: 99%
“…Adenovirus E1B-55K products also form aggregates in the nucleus, in particular under conditions that inactivate nucleocytoplasmic transport of Ad2/5 E1B-55K by the CRM1-mediated export pathway (Kra¨tzer et al, 2000;Endter et al, 2001Endter et al, , 2005Carter et al, 2003;Flint et al, 2005). Similar to cytoplasmic inclusion bodies, formation of the spherical nuclear aggregates is accompanied by the relocalization of p53, PML (Endter et al, 2005) and Mre11 ( Figures 7A and B).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, it has also been reported that the E4 Orf 6 NES failed to direct efficient export of a heterologous protein and that export of this E4 protein is insensitive to leptomycin B (26,58). Regardless of whether the E4 Orf 6 protein leaves the nucleus via the exportin 1 pathway, there is clear evidence that this export receptor does not mediate export of viral late mRNAs: the inhibition of exportin 1 by leptomycin B or an NES containing peptide had no effect on synthesis of viral late proteins (15,78) or viral late mRNA export (34).…”
mentioning
confidence: 97%